Strangers [videorecording (DVD)] = Zarim - Nattiv, Guy; Nattiv, Guy; Tadmor, Erez; Tadmor, Erez; Levo, Liron; Azabal, Lubna; Lollia, Dominique; Albenque, Patrick; El Akal, Abudalla, 1998- (KimStim, 2011)
A chance encounter in Berlin sparks an affair between an Israeli man and a Palestinian woman when handsome Eyal and gorgeous Rana meet when their backpacks get swapped on the subway during the 2006 World Cup finals, and over six days they get swept away by romantic desire, soccer mania, and competing political loyalties, but when Rana suddenly returns to Paris, Eyal must make some bold choices that could alter their lives forever.